2014
DOI: 10.1021/nn505325w
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Contraction and Extension of Single Macromolecules on a Modified Graphite Surface

Abstract: Synthetic rigid-rod polymers incorporating multiple azobenzene photoswitches in the backbone were deposited from solution onto a monolayer of octadecylamine covering the basal plane of graphite. Large contractions and extensions of the single macromolecules on the surface were induced by irradiation with UV and visible light, respectively, as visualized by scanning force microscopy. Upon contraction, the single polymer chains form more compact nanostructures and also may move across the surface, resembling a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The synthesis of rigid‐rod azobenzene‐containing poly( para‐ phenylene) backbones is one strategy to maximize photo‐deformation, enabling accordion‐like compression and extension of chains upon cycling with UV and visible light ( Figure a) . Lee et al demonstrated that these single‐chain polymeric assemblies may even exhibit crawling movements when deposited onto a graphite surface modified with octadecylamine, and imaged with scanning force microscopy (Figure b) . Chemically or physically cross‐linked supramolecular assemblies of these linear photo‐mechanical polymers may be envisioned to lift weights, behave as actuators, and to perform other types of directed work with greater resistance against deformation fatigue than individual strands .…”
Section: Building Some ‘Real’ Light‐powered Molecular Devicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis of rigid‐rod azobenzene‐containing poly( para‐ phenylene) backbones is one strategy to maximize photo‐deformation, enabling accordion‐like compression and extension of chains upon cycling with UV and visible light ( Figure a) . Lee et al demonstrated that these single‐chain polymeric assemblies may even exhibit crawling movements when deposited onto a graphite surface modified with octadecylamine, and imaged with scanning force microscopy (Figure b) . Chemically or physically cross‐linked supramolecular assemblies of these linear photo‐mechanical polymers may be envisioned to lift weights, behave as actuators, and to perform other types of directed work with greater resistance against deformation fatigue than individual strands .…”
Section: Building Some ‘Real’ Light‐powered Molecular Devicesmentioning
confidence: 99%
“…The functionalization or tethering of the polymer strands to scaffolds may enable the macromolecules to perform work by lifting weights or transporting cargo. Reproduced with permission . Copyright 2014, American Chemical Society.…”
Section: Building Some ‘Real’ Light‐powered Molecular Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have highlighted earlier the exciting opportunities associated with the on-command reversible binding of biological ligands to [ 41 ] Copyright 2014, American Chemical Society.…”
Section: Light-induced Modulation Of Glycooligomers Binding Affi Nitiesmentioning
confidence: 99%